Head first Web design - Watrall, Ethan (Head first series., 2009)
Whether you are building a personal blog or a corporate website, there is a lot more to web design than div's and CSS selectors, but what do you really need to know? With this book, you'll learn the secrets of designing effective, user-friendly sites, from customer requirements to hand-drawn storyboards all the way to finished HTML and CSS creations that offer an unforgettable online presence.